Mothers’ Perceptions of the Role of Exclusive Breastfeeding in Preventing Stunting in Toddlers - Isnariyati, Eny; Hasibuan, Rachma (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Stunting is a serious nutritional issue that affects children's physical growth and cognitive development. It can be prevented through adequate exclusive breastfeeding during the first six months of life. This study aims to assess mothers’ perceptions regarding the importance of exclusive breastfeeding in preventing stunting among toddlers aged 6–24 months, as well as the factors influencing their decision to provide exclusive breastfeeding. The study sample consisted of 130 mothers with toddlers aged 6–24 months. Data were collected through interviews using structured questionnaires. Data analysis was conducted using descriptive statistics and logistic regression. The results showed that a positive maternal perception of exclusive breastfeeding was significantly associated with lower stunting rates among toddlers. Moreover, maternal knowledge and family support emerged as key factors contributing to the success of exclusive breastfeeding.